2015
DOI: 10.1155/2015/293802
|View full text |Cite
|
Sign up to set email alerts
|

Primary Intracranial Melanoma with Early Leptomeningeal Spread: A Case Report and Treatment Options Available

Abstract: Primary CNS melanomas are rare and they constitute about 1% of all cases of melanomas and 0.07% of all brain tumors. These tumors are aggressive in nature and may metastasise to other organs. Till date less than 25 cases have been reported in the literature. The primary treatment for local intraparenchymal tumours is complete resection and/or radiotherapy and it is associated with good survival. However once there is disease spread to leptomeninges the overall median survival is around 10 weeks. In this case r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 25 publications
0
48
1
Order By: Relevance
“…Amelanotic melanoma and melanoma without a hemorrhagic component tend to appear iso-long signal on T1WI and moderately long signal on T2WI. [ 17 ] Most of the lesion of our case was old intratumoral hemorrhage, appearing on MRI short T1 and long T2 signals, which was also somewhat different from previous cases.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Amelanotic melanoma and melanoma without a hemorrhagic component tend to appear iso-long signal on T1WI and moderately long signal on T2WI. [ 17 ] Most of the lesion of our case was old intratumoral hemorrhage, appearing on MRI short T1 and long T2 signals, which was also somewhat different from previous cases.…”
Section: Discussioncontrasting
confidence: 72%
“…Primary cerebral melanomas are supposed to be treated by complete resections plus effective postoperative radiochemotherapy. [ 17 , 18 ] In recent years, the most effective and common chemotherapy drug is dacarbazine, which could be used after operation or radiotherapy, presenting the effectiveness rate of 16% to 20%. [ 3 ] Previously, some researches indicated that stereotaxic radiosurgery (SRS), alone or plus whole-brain radiotherapy, might improve lifespans of cerebral melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Melanomas do not stain for epithelial membrane antigen (EMA), and this differentiates it from meningioma. Our patient’s tumor also showed positivity for HMB-45 and S 100 and was negative for EMA [ 5 ]. It also had features suggestive of necrosis and increased mitotic activity with cellular atypia more favouring a malignant process.…”
Section: Discussionmentioning
confidence: 99%
“…Complete surgical removal of the intracranial tumor is the mainstay of management. The adjuvant treatment options include radiotherapy (focal, whole brain or craniospinal) depending on the extent of the disease at presentation [ 5 ]. Intrathecal and systemic chemotherapy was tried by various researchers with some benefit in metastatic melanoma, but not in primary leptomeningeal melanoma [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary malignant melanomas of the central nervous system (CNS) represent only 1% of all melanomas and as little as 0.07% of all brain tumors. 1 To date, the relevant literature has reported < 30 cases [1][2][3] that can be classified with relative certainty as primary malignant CNS melanomas. Primary amelanotic melanomas are even rarer (►Table 1).…”
Section: Introductionmentioning
confidence: 99%